Pengaruh Harga, Produk, Lokasi dan Promosi terhadap Minat Beli pada PT. Medico Global Pratama Bandar Lampung - Aryando, Praditya; Surya, Andi; Desmon, Desmon; Yudhinanto, Yudhinanto; Hasbullah, Hasbullah; Sari, Evi Meida (Penerbit Goodwood, 2024)
Purpose: To determine the influence of marketing on price, product, location, and promotion of purchasing interest in trading companies with coal as a commodity. Methodology: The data used in this study were qualitative. The primary data source used was based on the source, and this type of primary research data can be obtained by researchers directly from the data source. A total of 46 samples were used in this study. The data collection techniques used were interviews/questionnaires, documentation, and literature review. This study consists of two variables: the independent variable (X1) price, (X2) product, (X3) location, (X4) promotion, and the attachment variable (Y) Purchase Interest. The analytical tool uses the classic assumption test, which consists of validity and reliability tests, normality tests, heteroscedasticity tests and correlation tests, multiple linear regression tests, hypothesis tests consisting of coefficient of determination tests, F tests, and T tests, and the SPSS analysis tool version 23. This research was conducted at the Medico Global Pratama Company. Results: Price, Product, Location and Promotion variables have a positive and significant effect on purchase interest in PT. Medico Global Pratama Lampung. Limitations: The problem is limited to the simultaneous influence of price, product, location, and promotion on purchasing interest in PT. Medico Global Pratama Lampung. Contributions: Data sources were searched, articles were assessed, results were reported, and the published paper was drafted.